Analysis of the Determinants for Credit Distribution in Conventional and Digital Banks Listed in the Indonesian Stock Exchange - Asyrafi, Muhammad Mirza; Farah Wulandari Pangestuty (Contemporary Studies in Economic, Finance and Banking, 2026)
This research analyzes the factors that drive credit distribution in conventional and digital banking in Indonesia. Amidst the digital transformation era, this research specifically tests the credit policy determinants for both business models. Using separate panel data regres-sions on 26 banks during the 2020-2023 period, it was found that Third-Party Funds (DPK) is a main driver for both groups, confirming the basic intermediation function. However, a fundamental strategic difference was also identified: digital banks' credit distribution is significantly spurred by capital strength (CAR). Meanwhile, for conventional banks, the primary significant driver is the availability of customer funds (DPK), while the profitability incentive (NIM) was found to be insignificant. This finding implies that the strategy of digi-tal banks focuses on aggressive capital-based expansion, while conventional banks oper-ate more conservatively and traditionally.